Thiophene derivative inflicts cytotoxicity via an intrinsic apoptotic pathway on human acute lymphoblastic leukemia cells. - Risa Mia Swain; Anahi Sanchez; Denisse A Gutierrez; Armando Varela-Ramirez; Renato J Aguilera (PLoS ONE, 2023)
In an effort to identify novel anti-cancer agents, we employed a well-established High Throughput Screening (HTS) assay to assess the cytotoxic effect of compounds within the ChemBridge DIVERSet Library on a lymphoma cell line. This screen revealed a novel thiophene, F8 (methyl 5-[(dimethylamino)carbonyl]-4-methyl-2-[(3-phenyl-2-propynoyl) amino]-3-thiophenecarboxylate), that displays anti-cancer activity on lymphoma, leukemia, and other cancer cell lines. Thiophenes and thiophene derivatives have emerged as an important class of heterocyclic compounds that have displayed favorable drug characteristics. They have been previously reported to exhibit a broad spectrum of properties and varied uses in the field of medicine. In addition, they have proven to be effective drugs in various disease scenarios. They contain anti-inflammatory, anti-anxiety, anti-psychotic, anti-microbial, anti-fungal, estrogen receptor modulating, anti-mitotic, kinase inhibiting and anti-cancer activities, rendering compounds with a thiophene a subject of significant interest in the scientific community. Compound F8 consistently induced cell death at a low micromolar range on a small panel of cancer cell lines after a 48 h period. Further investigation revealed that F8 induced phosphatidylserine externalization, reactive oxygen species generation, mitochondrial depolarization, kinase inhibition, and induces apoptosis. These findings demonstrate that F8 has promising anti-cancer activity.